The Effects of MIS Treatment on Suppressing the Proliferation of Ectopic Endometrial Cell Lines - Karipcin, Sinem F.; Lu, Fangxian; Borahay, Mostafa; Kilic, Sami G.; Bilgin, Gurates (Sage Publications Inc, 2010)
[Abstract Not Available]
57th Annual Meeting of the Society-for-Gynecologic-Investigation -- MAR 24-27, 2010 -- Orlando, FL